Impacts of the COVID-19 pandemic on HIV care and treatment services among adolescents attending a tertiary hospital in Dar es Salaam, Tanzania: a qualitative study - Agricola Joachim; Dorkasi L Mwakawanga; Lilian Nkinda; Eva Kidabulo (BMJ Public Health)
Background The COVID-19 pandemic has caused substantial disruption on HIV care and treatment programmes, especially for adolescents living with HIV (ALHIV) who are known to have poorer health outcomes compared with adults. Efforts made to overcome the pre-existing challenges were hampered by the emergence of the pandemic which interrupted adolescent-friendly healthcare services. Therefore, the aim of this study was to assess the impacts of the pandemic on HIV care and treatment services from healthcare providers and adolescents’ experiences at a tertiary hospital in Dar es Salaam, Tanzania.Methods A descriptive qualitative study using in-depth interviews was conducted with 17 study participants. Purposive and convenient sampling techniques were used to recruit healthcare providers and adolescents, respectively. Swahili semistructured interview guide was used to conduct interviews. Thematic analysis was conducted to generate themes and subthemes describing the experiences on effects brought by COVID-19 on HIV care and treatment among adolescents.Results The study revealed that alteration of approach in delivery of healthcare and limited human and non-human resources in healthcare facilities during the COVID-19 pandemic decreased effectiveness and quality of care which resulted in adolescent’s poor adherence to medication and loss to follow-up. Loss of family income, food insecurity and limited socialisation posed threat to adolescent’s mental health and overall quality of life.Conclusion Our findings underscore the impacts of COVID-19 and its immediate responses that significantly affected adolescent HIV care and treatment services. Reinforcement of sustainable ALHIV programmes and funding supports to these programmes are essential to promote retention and engagement to care during pandemics.